CHROMOBLASTOMYCOSIS: A RARE PRESENTATION WITH POLYMORPHIC CUTANEOUS LESIONS AND BONE INVOLVEMENT, CAUSED BY EXOPHIALA JANSELMEI - Rehman, Batool ur; Maria Mansoor; Humaira Talat; Reema Mirza; Farheen Ishfaq (Journal of Ayub Medical College Abbottabad, 2023)
Chromoblastomycosis, a chronic fungal infection of skin and subcutaneous tissue arises as a result of traumatic inoculation of exposed areas of body. We present a unique case of chromoblastomycosis caused by Exophiala janselmei in a female farmer who presented with multiple smooth non tender nodules on trunk and limbs for 5 years and pigmented indurated plaques on face for 2 years along with deformities of hands. Imaging investigations revealed multiple lytic lesions in the bones of upper and lower limbs. Histopathological findings showed characteristic sclerotic bodies, consistent with the diagnosis of chromoblastomycosis. She was started on combination of oral antifungals with good response. This case highlights the importance of high suspicion and early diagnosis of deep fungal infections in order to avoid disfigurement and comorbidities.